No Need for Certainty? - Percy, Martyn (Reviews in religion and theology, 2025)
This review article explores the long-term consequences for churches in trying to establish biblical truth claims as equally valid to those of science. The impact on children's education is examined, as it becomes apparent that religious accounts for the origins of life and the universe are regarded as tales and fables might be. This further undermines trust and confidence in the churches, especially when Christians seek to assert that their claims may be regarded as matters of certainty.